THE EFFECTIVENESS OF USING COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO TEACH READING SKILL - Sugianto; Muhammad Asrul Hasby (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The research is entitled “The effectiveness of using cooperative integrated reading and composition (CIRC) method to teach reading skill”. The research is aimed to find out the answer of research question that reads “Is using Cooperative Integrated Reading and Composition (CIRC) Method more effective than that of using conventional method to teach reading skill” The research was an experimental research method in which the researcher compared two groups, experimental and control groups that are given different treatment during the research process. The experimental group was taught by using Cooperative Integrated Reading and Composition (CIRC) Method, meanwhile the control group was taught by using conventional reading method, in this case silent reading method. The result of post-test obtained by both groups was taken as the effect of the different treatment given for both groups. The result of this research shows that teaching reading skill by using CIRC Method was more effective than teaching reading skill by using conventional method. The effectiveness of using CIRC Method to teach reading skill was proved by the research findings that show the mean score of experimental group was 83.5 higher than mean score of control group 64. The result of t-test (t-calculation) was 1.90 higher than the value of t-table = 1.684 at level of significance 5% (0.05).